PROFIL PEMBELAJARAN TEMATIK BERBASIS TRADISI LOKAL “GAWAI DAYAK” DALAM MEMBENTUK KARAKTER PELAJAR PANCASILA PADA SISWA SEKOLAH DASAR DI KECAMATAN BINJAI HULU KABUPATEN SINTANG - Paskarada Gerada; Tahmid Sabri; Tati Rajati (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This research aimed to describe lesson plan, the implementation of learning that lesson plan, the  process of assessment, learning outcomes, supporting and inhibiting factors, and to describe the teachers’ and students’ responses and to describe the role of thematic learning based on local Dayak traditions in establishing the character of Pancasila for students. This is a descriptive research was carried out at SDN 12 Sungai Risap, SDN  04 SPF Mensiku and SDN 07 Telaga II, within the teachers, principals, and 4th grade students as the subjets. The findings of this research showed that are 1) the teachers had already planned the local tradition-based thematic learning well; 2) the teachers also had already performed 5 essential steps well, i.e. observing, asking, exploring, associating, and communicating; 3) the teachers had assessed the learning within the assessment procedure as showed by Curriculum of 2013; 4) the learning outcomes showed that the students could achieve the determined basic competencies through students’ knowledge, attitude, and skills; 5) there were some supporting and barrier factors for the students in order to achieve the basic competencies. The supporting factors were competent teachers, media, method, material, students’ interest, and environmental condition for studying, meanwhile the barrier factors were limited time, limited media, and students’ interest; 6) the teachers and students positively responded the implementation of local tradition ‘Gawai Dayak’ thematic learning-based. They stated that it was easy to understand because it was from their real experience in society; 7)  ‘Gawai Dayak’ tradition-based thematic learning played role to establish the characters of students of Pancasila. Some of the characters were noble moral character (to the God, nature, and other human beings), global diversity character and mutual cooperation character.